Low‐Temperature Synthesis of Large‐Scale Molybdenum Disulfide Thin Films Directly on a Plastic Substrate Using Plasma‐Enhanced Chemical Vapor Deposition. (10th August 2015) - Ahn, Chisung; Lee, Jinhwan; Kim, Hyeong‐U; Bark, Hunyoung; Jeon, Minhwan; Ryu, Gyeong Hee; Lee, Zonghoon; Yeom, Geun Young; Kim, Kwangsu; Jung, Jaehyuck; Kim, Youngseok; Lee, Changgu; et al.
<x xml:space="preserve">Abstract</x> By plasma‐enhanced chemical vapor deposition, a molybdenum disulfide (MoS2) thin film is synthesized directly on a wafer‐scale plastic substrate at below 300 °C. The carrier mobility of the films is 3.74 cm2 V−1 s−1. Also, humidity is successfully detected with MoS2‐based sensors fabricated on the flexible substrate, which reveals its potential for flexible sensing devices.